DEATH IDEAS IN PLATH’S SELECTED POEMS AND ITS RELATION TO POET’S SUICIDE: FORENSIC LINGUISTICS STUDY - Faradika, Vicha (Universitas PGRI Sumatera Barat, 2019)
This article describes death ideas which occur in Sylvia Plath’s selected poems entitled “Full FathomFive”,“I am Vertical”, “Ariel” and “Edge” which focused on their relation to poet’s depression evidence before committing suicide. It can be used to investigate poet’s suicide case in perspective of forensic linguistics. This is a qualitative research that is conducted by using L.G. Alexander’s poetic devices and theory of suicide by Durkheim to analyse Plath’s suicidal motives. The result of the analysis shows that Plath’s suicidal motives are basically oriented to the stage of self-destruction due to the changing ideas of death from the selected poems from death as unacceptable thing, an unavoidable choice, gate for a rebirth to final solution of all life's problems. It is caused by personal feeling that completely separate from community.Keywords: death, sicide, poem, forensic linguistics